1996
DOI: 10.1074/jbc.271.40.24728
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction in Vitro and in Vivo of Glyceraldehyde-3-phosphate Dehydrogenase and LA Protein with Cis-acting RNAs of Human Parainfluenza Virus Type 3

Abstract: Human parainfluenza virus type 3 (HPIV3) genome RNA is transcribed and replicated by the virus-encoded RNA-dependent RNA polymerase, and specific cellular proteins play a regulatory role in these processes. To search for cellular proteins potentially interacting with HPIV3 cis-acting regulatory RNAs, a gel mobility shift assay was used. Two cellular proteins specifically interacted with the viral cis-acting RNAs containing the genomic 3 -noncoding region and the plus-sense leader sequence region. Surprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 38 publications
1
92
0
1
Order By: Relevance
“…Construction of two plasmids containing the 73-nt 3Ј genomic-sense (3Ј-GS) and leader sense (LS) RNAs, respectively, under control of the T7 promoter was described earlier (11). Radiolabeled RNAs were synthesized using these plasmid DNAs after linearization with HgaI in an in vitro transcription reaction mixture containing 500 M each ATP, GTP, and CTP; 25 M UTP; 50 Ci of [␣- 32 P]UTP; and 20 U of T7 RNA polymerase in a 50-l volume in accordance with the manufacturer's (Boehringer Mannheim) protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction of two plasmids containing the 73-nt 3Ј genomic-sense (3Ј-GS) and leader sense (LS) RNAs, respectively, under control of the T7 promoter was described earlier (11). Radiolabeled RNAs were synthesized using these plasmid DNAs after linearization with HgaI in an in vitro transcription reaction mixture containing 500 M each ATP, GTP, and CTP; 25 M UTP; 50 Ci of [␣- 32 P]UTP; and 20 U of T7 RNA polymerase in a 50-l volume in accordance with the manufacturer's (Boehringer Mannheim) protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, comparison of the nucleotide sequences of different paramyxovirus 5Ј-and 3Ј-terminal RNA sequences identified highly conserved regions which may form the cognate site for binding of cellular proteins (50). In the case of HPIV3, we recently reported that cellular glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and La protein interact with the viral cis-regulatory RNAs (11). Further analysis revealed that these cellular proteins are also packaged within the progeny virions, suggesting a role(s) for these cellular proteins in HPIV3 transcription and replication.…”
mentioning
confidence: 99%
“…It has previously been reported that GAPDH is localized in the perinuclear region and in polysomes in addition to its well-documented localization in the cytoplasm (De et al, 1996). Our investigations revealed that GAPDH is the major cytoplasmic (S-100) RNA-binding activity of BSC-1, HeLa and FRhK-4 cells, and that its association with ribosomal components (RSW) highly impaired this activity.…”
Section: Discussionmentioning
confidence: 62%
“…Specific binding of GAPDH to AU-rich elements (AREs) in the 39NTRs and association with polysomes has led to the suggestion that the protein may play a role in both regulation of ARE-dependent turnover and translation of mRNA (Nagy & Rigby, 1995). Furthermore, De et al (1996) demonstrated that GAPDH and La protein interact with two cis-acting RNAs of human parainfluenza virus type 3. Both RNAs contain AU-rich sequences and have the potential to form similar stem-loop structures.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the La autoantigen, which has been found to be associated with the 3ЈUTR (Ϫ) of Sindbis virus (32) and parainfluenza virus (10) in conjunction with glyceraldehyde-3-phosphate dehydrogenase. Some uncharacterized cellular proteins with molecular masses of 42 and 44 kDa, 36 and 38 kDa, and 108, 60, 50, and 42 kDa can stably bind to the 3ЈUTR (Ϫ) of Sindbis virus (31), poliovirus (35), and West Nile virus (38), respectively.…”
mentioning
confidence: 99%